1963
DOI: 10.1111/j.2044-8260.1963.tb00372.x
|View full text |Cite
|
Sign up to set email alerts
|

The Measurement of Religious Attitudes in a University Population

Abstract: A scale was constructed for measuring the religious attitudes of students at a British University. Scores obtained from administration of the scale to a representative sample of 500 students show that there is a significant decline in religious belief among students in the Faculties of Arts and Pure Science during early years at the University, but that this decline continues only for the Science students, especially those who later engage in research. Medical students in their final years and students trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

1964
1964
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 5 publications
0
19
0
1
Order By: Relevance
“…It is necessary, then, to pay attention to specific elements of faith and religious practice. Almost all descriptions and measures centering around religious faith and practices duly do this (e.g., Brown & Lowe, 1951;Francis, 1978;Gill & Thornton, 1989;Greer & Francis, 1992 1965; Poppleton & Pilkington, 1963). As noted by Lewis, Cruise, and Lattimer (2007), Francis's (1978) Scale of Attitude Toward Christianity is so popular that it has featured in more than 200 studies on religiosity.…”
Section: Religious Faith and Practicesmentioning
confidence: 95%
See 1 more Smart Citation
“…It is necessary, then, to pay attention to specific elements of faith and religious practice. Almost all descriptions and measures centering around religious faith and practices duly do this (e.g., Brown & Lowe, 1951;Francis, 1978;Gill & Thornton, 1989;Greer & Francis, 1992 1965; Poppleton & Pilkington, 1963). As noted by Lewis, Cruise, and Lattimer (2007), Francis's (1978) Scale of Attitude Toward Christianity is so popular that it has featured in more than 200 studies on religiosity.…”
Section: Religious Faith and Practicesmentioning
confidence: 95%
“…For the sake of scientific convenience and parsimony, these can be clustered in two main categories: (a) unidimensional and (b) multidimensional measurement schemes. Within the former, religiosity is typically studied in terms of discrete elements distributed among, but not limited to, religious beliefs and practices (e.g., Brown & Lowe, 1951;Gill & Thornton, 1989;Lee, 1965), attitudes toward religion (e.g., Francis, 1978;Greer & Francis, 1992;Poppleton & Pilkington, 1963), religious orientation (e.g., Allport & Ross, 1967;Gorsuch & McPherson, 1989;Ryan, Rigby, & King, 1993), religious commitment and experience (e.g., Hood, 1970;Pfeifer & Waelty, 1995;Roof & Perkins, 1975), and religious development (e.g., Fowler, 1981;Malony, 1988). From the second perspective, religiosity is understood in terms of a discrete unidimensional component, which is developed into multidimensional religiosity statements as it seems prominent, for instance, in the case of attitudes toward religion (e.g., Funk, 1958;Maranell, 1974) or religious experiences and beliefs (e.g., Boan, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…(3) Assessment of subject's religious attitudes. The scale used was one constructed by Poppleton & Pilkington (1963) to measure religious attitudes in a British university population. Since the scale was specifically designed to measure religious attitudes, it was necessary to make certain assumptions regarding the attitude towards the church of high, intermediate and low Scorers on the scale.…”
Section: 'mentioning
confidence: 99%
“…The evidence of whether the trend away from religion applies equally to religious beliefs and practices is split. Poppleton and Pilkington (1963) found that both are almost equally affected, whereas Watkins ( 1 979) concluded that only religious practice was declining among students at an Australian university from 1965 to 1977. McCallum (1 986) reviewed the dynamics of secularization in Australia and noted that on the basis of cross-sectional surveys the following indicators of religion have declined during the past 20 years in Australia: church affiliation, church attendance, strength of belief in God, prayer, religious vocations among Catholics, and church control over marriage.…”
mentioning
confidence: 99%